Structural reliability simulation for the latching mechanism in MEMS-based Safety and Arming device. (June 2017) - Tu, Hongmao; Lou, Wenzhong; Sun, Zhili; Qian, Yunpeng
Highlights: An efficient MEMS structural reliability simulation method is presented. We propose an efficient CAE software integration method for reliability simulation. We evaluate the reliability of the latching mechanism in a MEMS Safety and Arming device. We perform the sensitivity analysis to identify the significant random variables. Some improvement measures are proposed for the latching mechanism of interest. Abstract: Based on the deterministic performance analysis of latching mechanism in MEMS (micro-electro-mechanical system)-based Safety and Arming device (S&A device), probabilistic algorithms and Kriging approximation method coupling with finite element simulation are used to quantify the effect of input uncertainties on the response metrics of the mechanism. It firstly uses performance function to represent the failure of the latching mechanism mathematically, and then constructs the corresponding reliability model according to structural reliability theory. In order to relieve the burden of further reliability and sensitivity calculations, Kriging interpolation technique is adopted to approximate the performance function and hence simplify the reliability model. Samples of input variables and the corresponding response, which all together serve as the inputs of Kriging approximation, are gotten through finite element simulations based on the design of experiments. An efficient CAE software integration method is proposed to facilitate the repetitive FE-based calculations of those samples. Finally, FORM (First Order Second Moment Method) is utilized to get the reliability index and its sensitivities with respect to the input random variables and their parameters, which can not only be employed for reliability assessment of the latching mechanism, but also can help to identify key factors for additional structural improvements.